Acceptability of Functional Behavioral Assessment Procedures to Special Educators and School Psychologists. (November 2015) - O'neill, Robert E.; Bundock, Kaitlin; Kladis, Kristin; Hawken, Leanne S.
This survey study assessed the acceptability of a variety of functional behavioral assessment (FBA) procedures (i.e., functional assessment interviews, rating scales/questionnaires, systematic direct observations, functional analysis manipulations) to a national sample of 123 special educators and a state sample of 140 school psychologists. Results indicated that special educators and school psychologists reported generally positive perceptions regarding their willingness to participate in, the appropriateness of, the usefulness of, and the feasibility of the FBA procedures. Special educators were significantly more likely to endorse the use of systematic direct observation and functional analysis manipulation strategies than school psychologists, although no differences were found regarding the social desirability of FBA procedures for individuals exhibiting mild and severe problem behaviors. School psychologists were also more likely than special educators to express concerns about the amount of time that can be entailed in FBA procedures. We discuss implications for practice and future research.